PROBLEM TEACHING TECHNOLOGY IN RUSSIAN LANGUAGE CLASSES - Nodirova Go‘zaloy Ravshanbekovna (Journals Park Publishing, 2023)
In this article, attention to learning and teaching foreign languages in our country, in particular, problematic teaching technology in Russian language classes was discussed.
Keywords: foreign language, study, Russian language, program, tool, cognitive, solution, problem.